Enforcing Multi-user Security Policies in Cloud Computing - Shubhada Parashar Mone; Sunita S. Dhotre (Institute of Advanced Engineering and Science, 2013)
The user can access data from any server with unlimited data with the security. Multi-user tendency will cost lesser than the expected cost in the single user environment. While dealing with cloud computing, confidential data can be secured from the unauthorized access and internal threats. Cloud servers use smart techniques for achieving this requirement like encryption and decryption of data. The database is stored in the encrypted format on the server & a complex query can be fired on it. Cloud server will maintain the access control policies to reveal the data from the database that are in the encrypted format. In the access control policies, we use KMA (Key Management Authority) which provides the keyset for encryption & decryption of the database. The attributes entered by the user will create one public key which is cipher text based. So this technique is called as cipher text based technique. This key is used for encryption. While registering, user will choose the policy and select the attributes on which security policy is based. Because of this it is called as cipher text policy attribute based encryption (CP-ABE). To achieve this complex encryption, we can use many algorithms like AES or DES encryption algorithms with CPABE algorithm. This scheme allows making SQL-like queries on encrypted database in multiuser environment while at the same time, the database owner assign different access rights to users that defines a specific policy for the database. The major use of this encryption is privacy, access control and data confidentiality and multi-user access control.DOI:http://dx.doi.org/10.11591/ijece.v3i4.3061